SGLT2 inhibitors and cirrhosis: A unique perspective on the comanagement of diabetes mellitus and ascites. Issue 6 (26th July 2018) - Saffo, Saad; Taddei, Tamar
Abstract : Watch a video presentation of this article Answer questions and earn CME